The performance of immigrants in the German labor market - Robert Beyer (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper uses a large survey (SOEP) to update and deepen our knowledge about the labor market performance of immigrants in Germany. It documents that immigrant workers initially earn on average 20 percent less than native workers with otherwise identical characteristics. The gap is smaller for immigrants from advanced countries, with good German language skills, and with a German degree, and larger for others. The gap declines gradually over time but at a decreasing rate and much stronger for more recent cohorts. Less success in obtaining jobs with higher occupational autonomy explains half of the wage gap. Immigrants are initially less likely to participate in the labor market and more likely to be unemployed. While participation fully converges after 20 years, immigrants always remain more likely to be unemployed than the native labor force.
Keywords: E24; F22; J15; J22; J31; J61; 330; migration; Germany; labor market; wages; unemployment; participation